2020
DOI: 10.1002/jmri.27264
|View full text |Cite
|
Sign up to set email alerts
|

Brain Oxygen Extraction Is Differentially Altered by Alzheimer's and Vascular Diseases

Abstract: Background: Alzheimer's disease and vascular cognitive impairment (VCI), as well as their concurrence, represent the most common types of cognitive dysfunction. Treatment strategies for these two conditions are quite different; however, there exists a considerable overlap in their clinical manifestations, and most biomarkers reveal similar abnormalities between these two conditions. Purpose: To evaluate the potential of cerebral oxygen extraction fraction (OEF) as a biomarker for differential diagnosis of Alzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 39 publications
5
42
0
Order By: Relevance
“…2 One major strength of our study was our use of participant specific Y a , hematocrit, and hemoglobin values in the calculation OEF and CMRO 2 , which have often been assumed as reference values in previous studies associating brain health with TRUST MRI variables. 2,3,6 In models where CMRO 2 significantly related to an outcome, no CMRO 2 component variable was significantly related to the outcome, indicating that associations between CMRO 2 and outcomes were not driven by any single CMRO 2 component variable, highlighting the potential importance of capturing all such variables. Nonetheless, it is possible that regional CBF may explain associations between CMRO 2 and outcomes among APOE-e4 carriers even though the component variable grey matter CBF did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 One major strength of our study was our use of participant specific Y a , hematocrit, and hemoglobin values in the calculation OEF and CMRO 2 , which have often been assumed as reference values in previous studies associating brain health with TRUST MRI variables. 2,3,6 In models where CMRO 2 significantly related to an outcome, no CMRO 2 component variable was significantly related to the outcome, indicating that associations between CMRO 2 and outcomes were not driven by any single CMRO 2 component variable, highlighting the potential importance of capturing all such variables. Nonetheless, it is possible that regional CBF may explain associations between CMRO 2 and outcomes among APOE-e4 carriers even though the component variable grey matter CBF did not.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to cognitively unimpaired peers, older adults with mild cognitive impairment (MCI) have similar global CBF but lower global OEF and CMRO 2 . 2 As low OEF has been linked to increased amyloid burden, 6 and hypometabolism precedes atrophy in MCI, 7 low OEF and CMRO 2 may be important early correlates of an underlying Alzheimer's disease (AD) neurodegenerative process.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in MRI technology have allowed noninvasive and rapid measurements of OEF and metabolism on clinical MRI scanners, 36,51–59 providing a new opportunity to examine the utility of oxygen metabolism as a candidate biomarker in AD. Previous human studies have provided evidence that OEF and CMRO 2 can differentiate between patient populations and are correlated with cognitive function 12,14,15 . However, the associations between oxygen metabolism and major hallmarks of AD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cognitively normal carriers of the apolipoprotein E4 gene, which is a risk factor for AD, manifested lower global brain oxygen extraction compared with noncarriers 14 . Another report revealed that lower OEF was associated with poorer cognitive scores 15 . Therefore, brain oxygen metabolism may provide a rapid and noninvasive functional biomarker for neurodegeneration in AD.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JMRI, Jiang et al report a prospective cross-sectional study on changes in brain oxygen extraction fraction (OEF) in AD and vascular diseases, suggesting the OEF as a useful biomarker. 3 They based their study on the hypothesis that tissue metabolic demand is reduced in AD due to amyloidosis, tauopathy, and neurodegeneration, with preserved vascular function. In contrast, vascular disease is associated with reduced brain perfusion, and thus high OEF for metabolic needs.…”
mentioning
confidence: 99%